Examination of Social and Economic Factors Affecting Agricultural Development in Bamyan Province, Afghanistan - Ramazan Ahmadi (Sosyolojik Bağlam Dergisi)
This study investigates the social and economic factors influencing agricultural development in Bamyan province. Using a mixed-methods approach, the research combines quantitative and qualitative data collected through questionnaires, interviews, and focus groups. The study population includes farmers aged 18 to 93 from eight districts of Bamyan province. While questionnaires were primarily completed by men, interviews and focus groups ensured equal gender representation. Quantitative data were analyzed using SPSS, while qualitative data were analyzed using MAXQDA. Findings reveal that agriculture in Bamyan remains a male-dominated sector, though women contribute significantly to production. Mostly illiterate, farmers face challenges such as economic instability, climate change, and reduced external support. Despite these difficulties, agriculture remains central to the local economy, with key crops including potatoes, wheat, and fodder, alongside livestock and horticulture. However, market inefficiencies and weak structural support limit profitability. The decline in government and organizational assistance has exacerbated economic hardships, restricting access to resources and training. To address these issues, targeted investments in infrastructure, training programs, cooperatives, and market access are essential to enhance farmers’ incomes and ensure the sector’s sustainability.